2020
DOI: 10.1016/j.ygyno.2019.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of patients with POLE mutated endometrioid endometrial cancer

Abstract: Objectives: Assess outcomes of a clinical cohort of patients with endometrioid endometrial cancer (EEC) harboring somatic POLE exonuclease domain mutations (EDMs).Methods: Patients were consented to a protocol of tumor-normal massively parallel sequencing of 410-468 cancer related genes. EECs subjected to sequencing from 2014 to 2018 were reviewed. Tumors with somatic POLE EDMs were identified. EECs were assessed for microsatellite instability (MSI) using MSIsensor and immunohistochemical analysis for mismatch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 36 publications
1
23
0
1
Order By: Relevance
“…For example, in 1 single-institution study of n = 23 POLE endometrial cancers identified by cancer gene panel (MSK-IMPACT), 17% (4/23) were of advanced stage with extrauterine disease at the time of diagnosis, including 2 cases that were stage IV (distant metastasis). After a median follow-up of 30 months, 17% (4/23) of patients developed recurrences, of which 3 were distant metastases, including 2 brain metastases, and 1 patient died after 33 months (57). A separate large, multi-institutional study of POLE cancers by the NRG Oncology/Gynecologic Oncology Group found improved outcomes for the POLE group, but the differences were not statistically significant (58).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in 1 single-institution study of n = 23 POLE endometrial cancers identified by cancer gene panel (MSK-IMPACT), 17% (4/23) were of advanced stage with extrauterine disease at the time of diagnosis, including 2 cases that were stage IV (distant metastasis). After a median follow-up of 30 months, 17% (4/23) of patients developed recurrences, of which 3 were distant metastases, including 2 brain metastases, and 1 patient died after 33 months (57). A separate large, multi-institutional study of POLE cancers by the NRG Oncology/Gynecologic Oncology Group found improved outcomes for the POLE group, but the differences were not statistically significant (58).…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis described the histopathologic features and the prevalence of the ESMO risk category for each molecular subgroup and highlights that characteristics such as POLE mutation status and MMRd are more important than histologic features in prognostication [ 90 ]. However, 17% of POLE EC do recur after a median of 30 months follow-up [ 91 ]. The by far largest molecular group is the group of patients with NSMP tumours and almost half of the patients will be classified as such.…”
Section: Knowledge Gaps and Possible Solutionsmentioning
confidence: 99%
“…The mutation of POLE exonuclease domain, detected in 6–12% of endometrial cancers, 5 , 6 1–2% of colorectal cancers, 7 , 8 and less than 1% in gastric, breast, and brain cancer, 9 , 10 has emerged as one of the most promising candidate biomarkers. POLE encodes the catalytic subunit of DNA polymerase epsilon, which replicates the leading DNA strand before cell division.…”
Section: Discussionmentioning
confidence: 99%